Comparison between Sysmex CyFlow Counter and BD FACSCanto II + for counting CD4 Cells in Indonesia - Agus Susanto Kosasih; Hubertus Hosti Hayuanta; Nasuroh Nasuroh (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
CD4 count is essential in evaluating the immunological status of HIV+ patients and the need for prophylaxis therapy + against opportunistic infections. CyFlow Counter is a novel Sysmex instrument to count CD4 cells and reports the results in + + absolute and percentage values (aCD4 , %CD4 ). However, it has not been evaluated in Indonesia. This study aimed to compare the Sysmex CyFlow Counter with BD FACSCanto II. Samples were collected from leftover EDTA blood samples of + + + patients with CD4 count tested in Dharmais Cancer Hospital. The aCD4 and %CD4 from CyFlow Counter were compared against FACSCanto II using correlation, Bland-Altman, and mean difference test. Sensitivity, specificity, and misclassification rates were also analyzed with aCD4+ count threshold of 200 cells/µL. A total of 70 EDTA blood samples from Dharmais + Cancer Hospital were analyzed with BD FACSCanto II and Sysmex CyFlow Counter, with 20 subjects having CD4 count of 150-299 cells/µL, 28 having 300-449 cells/µL, and 22 having 450-550 cells/µL. CyFlow Counter had a good correlation + + with FACSCanto II in aCD4 and %CD4 (r = 0.892 [p=0.000], r=0.955 [p=0.000], respectively). There was no significant mean + + difference between CyFlow Counter and FACSCanto II (p=0.097 for aCD4 and p=0.611 for %CD4 ). Bland-Altman test + results showed a high agreement (94.29%) with a mean difference of -32.29 cells/µL for aCD4 and a high agreement + (98.57%) with a mean difference of -0.76% for %CD4 . Sensitivity, specificity, and total misclassification rates were 83.33%, + 100.00%, and 3.33%, respectively. Sysmex CyFlow Counter CD4 count results were comparable to FACSCanto II.